2020
DOI: 10.1159/000507100
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Questionnaire-Suitable Comorbidity Index in Patients Undergoing Radical Cystectomy

Abstract: Objective: To investigate the capability of a modified selfadministrable comorbidity index recommended in the standard sets for neoplastic diseases published by the International Consortium for Health Outcomes Measurement (ICHOM) to predict 90-day and long-term mortality after radical cystectomy. Methods: A single-center series of 1,337 consecutive patients who underwent radical cystectomy for muscle-invasive or high-risk non-muscle-invasive urothelial or undifferentiated bladder cancer were stratified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Among 891 patients with bladder cancer, the CCI predicted 5-year mortality [189]. In 1,337 patients who had radical cystectomy, the CCI predicted 5-year survival [190].…”
Section: Predictive Validitymentioning
confidence: 99%
“…Among 891 patients with bladder cancer, the CCI predicted 5-year mortality [189]. In 1,337 patients who had radical cystectomy, the CCI predicted 5-year survival [190].…”
Section: Predictive Validitymentioning
confidence: 99%
“…Leucocyte count was usually normal, with a mean of 8.4±4.1 x103 cells/µL. The mean CCI was 4.6±2.6 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The overall length of hospital stay ranged from two to 28 days, with an average of 10 days (excluding the two nosocomial cases).…”
Section: Resultsmentioning
confidence: 99%
“…Froehner et al validated it in patients with post-radical cystectomy who underwent radical cystectomy for muscle-invasive or high-risk non-muscle-invasive urothelial or undifferentiated bladder cancer after a five-year follow-up period. He studied 1,337 patients and compared CCI with a modified self-administrable comorbidity index that was based on standard sets for neoplastic diseases [ 11 ]. CCI was also found to predict outcomes in internal medicine-related complications post-hip arthroplasty after a mean 27-month follow-up period by Schmolders et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A good performance of the CCI and aCCI in mortality prediction is well documented in the current literature. Froehner et al reported an AUROC of 0.74 using the CCI to predict 90-day mortality in a larger cohort [25]. Prayer Galetti et al showed that the aCCI as a significant predictor of mortality in elderly patients undergoing RC [11].…”
Section: Discussionmentioning
confidence: 99%